The Underwater Quest of Prince Lee-Char: Renewing the Hero Archetype in Star Wars - Guitton, Matthieu J. (Journal of religion and popular culture, 2019)
The first three episodes of the fourth season of the animated series Star Wars: The Clone Wars describe the adventures of the young Prince Lee-Char, the Mon Calamari heir of the throne of the famous eponymous water world, as he struggles against the droid armies, engaging in a form of a rite of passage with mystical components. This aquatic tale can be analyzed on three distinct levels: a "macroscopic" perspective suggesting that this trilogy takes place in a specific context, a "microscopic" analysis exploring some specific elements of this quest as a form of pagan journey, and an intermediate "mesoscopic" point of view focusing on Prince Lee-Char as an individual and evaluating his function as a messianic figure. Drawing upon these three interconnected layers and the therianthropic nature of Prince Lee-Char, this article will explore how this underwater quest of Prince Lee-Char belongs to the logic of the Star Wars narrative and symbolic frameworks, yet how Prince Lee-Char, as a non-Force user and non-human character, renews the Star Wars hero archetype.